Wage going on ; Fantasy or reality ; Home is where your heart is [videorecording] - Lazaro, Cheche; Santos, Owen (The Probe Team, 1993)
Deals with wage hike by the labor sector; a six year old boy shooting his Nanny to death over a television program; and children's book publishing company.